1985
DOI: 10.1203/00006450-198501000-00032
|View full text |Cite
|
Sign up to set email alerts
|

IgD in Human Colostrum

Abstract: ABSTRACT. Simultaneous colostrum (C) and plasma samples (P) from 14 women, 1 to 5 days postpartum, were examined. Total IgD and specific IgD antibodies to & lactoglobulin, bovine serum albumin, Bermuda grass, and a-gliadin were measured by solid phase radioimmunoassay. The geometric mean concentrations of IgD were 35.8 (range 2.2-410) &dl for colostrum and 591.3 (range 72-4100) pgldl for plasma. Six subjects had a specific IgD antibody C/P ratio more than 10-fold greater than the total IgD C/P ratio, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Consistent with published studies (Keller et al, 1985), neither albumin nor IgG showed evidence of local concentration in breast milk. This is indicated by the high serum/milk (S/M) ratios in individual samples (Table 1, Fig.…”
Section: Immunoglobulin Classes and Albuminsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with published studies (Keller et al, 1985), neither albumin nor IgG showed evidence of local concentration in breast milk. This is indicated by the high serum/milk (S/M) ratios in individual samples (Table 1, Fig.…”
Section: Immunoglobulin Classes and Albuminsupporting
confidence: 91%
“…Certain disparities may be of importance. Keller et al, (1985) found more pronounced selective concentration of total IgD than we did, and marked individual differences between antibody ratios. Keller et al (1985) employed an entirely different panel of antigens including lactoglobulin, bovine serum albumin, Bermuda grass and alpha-gliadin in subjects who were presumptively exposed to the antigens naturally.…”
Section: >68mentioning
confidence: 57%
See 1 more Smart Citation
“…Investigations have failed to show local synthesis of IgE in the breast [118][119][120]. Although IgE may be detected in 40% of colostrum and milk samples, the concentrations are extremely low, and many samples of colostrum and milk contain no IgE activity when paired samples of serum contain high IgE levels.…”
Section: Ige and Igdmentioning
confidence: 99%
“…It has been suggested that nursing women with high serum IgD levels are more likely to have high IgD concentrations in their milk. The possibility of some local production of IgE and IgD cannot be ruled out [120].…”
Section: Ige and Igdmentioning
confidence: 99%